Assessing impact of fertilizer adoption in boosting small scale crop farming productivity in Sub-Saharan Africa - Murunga, Powel (International Association of Agricultural Economists, 2024)
The study examined the determinants of fertilizer adoption among small scale crop farmers across Sub-Saharan Africa's regions using a probit regression model and propensity score matching (PSM) technique to assess productivity impacts. Variables analyzed include land tenure, access to credit, access to fertilizer, gender, age, farm size, education, household size, expenditure, and other income sources. Data was obtained from households’ survey data for selected sub-Saharan countries. The countries were also categorized as arid, semi-arid, and non- arid regions. Findings indicated that access to fertilizer increases adoption across all zones, for example by 36.1% in arid areas at 95% confidence level. Access to credit is also significant at 95% confidence level in arid regions, boosting adoption by 6.2%. Land tenure positively affects adoption in semi-arid regions but is insignificant in arid and non-arid areas. Education levels and household expenditure show mixed effects; secondary education negatively affects adoption in arid zones, while higher household expenditure reduces adoption likelihood in semi-arid regions. The PSM analysis conducted showed that fertilizer adoption leads to increased productivity, with adopters experiencing yield increases between 195 kg/acre and 261 kg/acre compared to non- adopters. Policy recommendations to improve fertilizer adoption include enhancing supply chains for timely and affordable access, expanding financial services for smallholder farmers, securing land tenure, and providing targeted education and training programs. These strategies are expected to boost agricultural productivity and smallholder’s farmer livelihoods in arid and semi-arid regions. The study emphasizes on the critical role of fertilizer access in boosting productivity for smallholder farmers and provides actionable insights for policymakers to improve agricultural outcomes in challenging environments.